2001
DOI: 10.1001/archneur.58.6.921
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Distribution of Torsin A and Torsin B in Normal Human Brain

Abstract: Torsin A and torsin B have similar distribution in the central nervous system, although their subcellular localization is not identical. Strong expression in neuronal processes points to a potential role for torsin proteins in synaptic functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…This relationship is consistent with the normal role of this protein in cytoskeletal dynamics 1 and its immunostaining in axons. 3,4 However, the regional specificity of the DTI results is inconsistent with postmortem findings in which the distribution of torsin A immunostaining in DYT1 carriers was found to be essentially normal. 18,19 In summary, our data suggest that altered microstructural integrity of precentral motor pathways may constitute a vulnerability factor for the development of dystonia in DYT1 carriers.…”
Section: Discussionmentioning
confidence: 58%
“…This relationship is consistent with the normal role of this protein in cytoskeletal dynamics 1 and its immunostaining in axons. 3,4 However, the regional specificity of the DTI results is inconsistent with postmortem findings in which the distribution of torsin A immunostaining in DYT1 carriers was found to be essentially normal. 18,19 In summary, our data suggest that altered microstructural integrity of precentral motor pathways may constitute a vulnerability factor for the development of dystonia in DYT1 carriers.…”
Section: Discussionmentioning
confidence: 58%
“…In these and other studies, it is apparent that torsinA undergoes anterograde transport along neuronal processes to terminals, presumably in association with the ER and/or vesicles (12,(57)(58)(59), apparently mediated by kinesin. Ultrastructural studies in primate brain demonstrated torsinA immunoreactivity associated with small clear vesicles in symmetric synapses in the striatum (59).…”
Section: Nx(t/s) Asnmentioning
confidence: 54%
“…TorsinA is widely distributed throughout the central nervous system, and has been detected specifically in the cerebral cortex, striatum, substantia nigra pars compacta, thalamus, hippocampus, cerebellum, midbrain, pons and spinal cord (Augood et al, 1998(Augood et al, , 1999Shashidharan et al, 2000;Konakova et al, 2001;Rostasy et al, 2003). Within neurons, wild-type torsinA localizes to the endoplasmic reticulum (Liu et al, 2003;Naismith et al, 2004;Hewett et al, 2007), while mutant torsinA protein is found in the perinuclear space (Hewett et al, 2000;Gonzalez-Alegre and Paulson, 2004;Goodchild and Dauer, 2004).…”
mentioning
confidence: 99%